Outcomes in lung transplantation after prior major cardiothoracic procedures - Arvind Bakthavatsalam; Billanna Hwang; Michael S. Mulligan (JHLT Open)
Background: Lung transplantation (LTx) is a key treatment for end-stage pulmonary disease, yet survival lags other organ transplants. Prior major cardiothoracic (CT) may negatively affect short- and long-term outcomes but is not a contraindication to LTx. This study investigates the effect of prior major CT surgery on LTx short- and long-term outcomes. Methods: We retrospectively analyzed LTx patients between January 1, 2010 and October 1, 2018. Patients were stratified into Prior Major CT and No Major CT groups with charts evaluated for hospital length of stay (LOS), intensive care unit (ICU) LOS, ventilator duration, and survival between the 2 groups. Results: Of 426 patients identified, the No Major CT group had 378 patients and the Prior Major CT group had 48 patients. Median LOS, ICU LOS, and ventilator duration were 15 ± 2.2 days, 6 ± 2.3 days, and 2 ± 1.8 days in the Prior Major CT group compared to 16 ± 0.8 days, 5 ± 0.6 days, and 1 ± 0.4 days in the No Major CT group, respectively (p = 0.76, p = 0.23, p = 0.03). The Kaplan-Meier analysis showed 1-, 3-, and 5-year survival of 72.9%, 56.2%, and 50% vs 89.9%, 81%, and 73.3% in the Prior Major CT group vs the No Major CT group, respectively (p < 0.01). Conclusions: Major CT procedures have negative impacts on postoperative outcomes with a longer ventilator duration and worse long-term survival. Prior Major CT surgery should not necessarily be a contraindication for LTx, but a risk factor to be considered by clinicians when considering LTx candidacy.